Using Virtual Outcrop Models as a Geological Learning Media - M. Haris Miftakhul Fajar; Amien Widodo; Eko Puswanto; Marsha Khairia Alfany; Mahendra Wirayudhatama; Fikri Abdullah (Postgraduate, University of Mataram, 2023)
The Covid-19 pandemic has impacted various sectors due to a new wave of technology rising shortly, specifically geological learning models. Using research and development methods, the research aims to develop more scientific observations as a provision for pre-field work activities at Geophysical Engineering Department Institut Teknologi Sepuluh Nopember. Furthermore, we need a media that can provide learning that can emphasize process skills and students' abilities to determine and understand the objective concepts of material. Virtual outcrop models integrated with video learning platform can fulfil the learning process by providing experience in observations outcrops directly in the class. A three-dimensional (3D) Virtual Outcrop Model (VOMs) was created using the photogrammetry software Agisoft PhotoScan based on photos taken in the field using smartphones and drones. The existence of this media is expected to add direct experience to visualize how geological phenomena occur in nature. The learning activities are divided into four sequential stages: observation, data collection, interpretation, and hypothesis giving. 87% of respondents stated that learning models using VOMs and videos can boost their knowledge of scientific observation. This learning method can help improve academic achievement because it applies technology implementation in theory and practice, providing geological information to us